Structural design optimization and vibration assessment of a base frame for a 3 MW turbo compressor - Yarar, Eser; Makaraci, Murat; Yilmaz, Saban; Apsar, Omer; Kan, Esra (Acad Publ Pte Ltd - Singapore, 2025)
This study focuses on the design and analysis of a base frame for a 3 MW turbo compressor, aiming to develop a robust and reliable structural framework. The design process included comprehensive simulations, incorporating static stress-strain and dynamic vibration analyses to assess the base frame' performance under operational conditions. The static analysis evaluated the total deformation and strain behavior of the base frame, ensuring it can withstand the maximum load without yielding or excessive deformation. Dynamic vibration analysis was performed to identify the natural frequencies and potential resonance issues, minimizing the risk of vibrations that could compromise operational stability. Results from the static analysis revealed that the initial design exhibited a maximum total deformation of 0.24 mm, which was reduced to 0.09 mm in the final design-a 62.5% improvement. Elastic strain values were within safe operational limits for both designs. The effective mass ratio analysis showed significant results at frequencies close to 0 Hz, with negligible impact across the operating frequency range. Based on these analyses, an optimized base frame model was developed, meeting the design criteria for mechanical strength and vibrational stability. The results highlight the importance of integrating deformation, strain, and vibration assessments in the structural design of heavy-duty turbo compressor base frame, contributing to enhanced durability and performance.
Keywords: turbo compressor base frame; finite element method; stress-strain analysis; vibration analysis; structural optimization; dynamic simulation; TURBOCHARGER; Acoustics; Engineering; Mechanics